Impementasi CRM Untuk Meningkatkan Loyalitas Pelanggan Pada Layanan Catering - Al Amin, Imam Husni; ., Nur Hasan (Students Journal of Engineering, 2015)
Information technology has become a bridge to connect a wide variety of human needs. No doubt that human work was greatly helped by her presence. No exception in services business catering services. Internet making business catering services becomes increasingly growing rapidly because it can connect with the needs of service users are well-known catering company with the term CRM (Customer Relathionship Management).Catering company to build relationships with service users, may be increased either by the application CRM-based online catering. Hopefully with the application, Barokah Catering is the object of this study could serve ordering online. Where customers facilitated in making reservations, obtain information company, efficient, can give suggestions, comments, and complaints during this time can not be accommodated by the company. The company also benefited from customer loyalty can be maintained and is expected to attract new customers so that profits can be increased. With a web-based, information, data, and services can be delivered and handled in a short time. Keywords : information technology, catering, CRM, web programming